Hyperlipidemia-Associated Renal Damage Decreases Klotho Expression in Kidneys from ApoE Knockout Mice - Sastre, Cristina (Public Library of Science, 2013)
BACKGROUND: Klotho is a renal protein with anti-aging properties that is downregulated in conditions related to kidney injury. Hyperlipidemia accelerates the progression of renal damage, but the mechanisms of the deleterious effects of hyperlipidemia remain unclear. METHODS: We evaluated whether hyperlipidemia modulates Klotho expression in kidneys from C57BL/6 and hyperlipidemic apolipoprotein E knockout (ApoE KO) mice fed with a normal chow diet (ND) or a Western-type high cholesterol-fat diet (HC) for 5 to 10 weeks, respectively. RESULTS: In ApoE KO mice, the HC diet increased serum and renal cholesterol levels, kidney injury severity, kidney macrophage infiltration and inflammatory chemokine expression. A significant reduction in Klotho mRNA and protein expression was observed in kidneys from hypercholesteromic ApoE KO mice fed a HC diet as compared with controls, both at 5 and 10 weeks. In order to study the mechanism involved in Klotho down-regulation, murine tubular epithelial cells were treated with ox-LDL. Oxidized-LDL were effectively uptaken by tubular cells and decreased both Klotho mRNA and protein expression in a time- and dose-dependent manner in these cells. Finally, NF-κB and ERK inhibitors prevented ox-LDL-induced Klotho downregulation. CONCLUSION: Our results suggest that hyperlipidemia-associated kidney injury decreases renal expression of Klotho. Therefore, Klotho could be a key element explaining the relationship between hyperlipidemia and aging with renal disease.